2017
DOI: 10.4236/health.2017.92015
|View full text |Cite
|
Sign up to set email alerts
|

Do Birth Season and Sex Affect Adult Lung Function as Early Life Factors?

Abstract: Objectives: Although lung function decline is a normal ageing process, it can be potentiated by risk factors. However, the potential impact of early life factors on lung function decline has been scarcely studied. The aim of this study was to investigate the potential correlation between birth season and adult lung function. Methods: We enrolled 1008 South Korean patients (530 men and 478 women; age range, 40 -80 years) who were hospitalized for urological surgery, irrespective of respiratory disease. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Previous studies revealed relationships between birth month and asthma, attention-deficit/hyperactivity disorder, heart disease, and many other common medical problems [ 1 ]. In addition to asthma, considering the finding that male born in winter had lower lung function than male born in other seasons, the birth season may be an early life factor predicting lung function [ 2 ]. However, little is known about the relationship between urological diseases and the birth season.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed relationships between birth month and asthma, attention-deficit/hyperactivity disorder, heart disease, and many other common medical problems [ 1 ]. In addition to asthma, considering the finding that male born in winter had lower lung function than male born in other seasons, the birth season may be an early life factor predicting lung function [ 2 ]. However, little is known about the relationship between urological diseases and the birth season.…”
Section: Introductionmentioning
confidence: 99%